運用問題導向學習法提升國中學生學習成效之研究 －以人文通論地理結合校本課程為例 Enhance Learning Efficiency in Junior High Schools through Problem-based Learning: The Example of Human Geography in a School-based Curriculum - 葉宜宣 Yi-Hsuan Yeh (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan)
近年由基層老師發起的翻轉教室教學法如雨後春筍般出現，然而全面實施時發現並不適用於所有課程及學生。問題導向學習法以學生為中心，透過老師引導並搭配微講述，利用真實問題與學生建立共鳴，可發現運用於人文通論地理的研究甚少，因此本研究利用行動研究法，探究問題導向學習法於國中七年級下學期臺灣人文通論地理的教學實踐情形，並透過準實驗研究法，實驗組實施問題導向學習法，對照組實施傳統講述教學，藉以探討問題導向學習法是否能提升學生的學業成就，最後利用問卷調查法，分析學習態度是否有所差異。研究結果發現多數學生對於問題導向學習法給予正向的肯定，相較以往更主動閱讀課文，理解能力進步許多，各組發表時能分析學習的癥結點。再者，雖然實驗組整體成績無明顯提升，但部分中間程度學生進步顯著，可是隨著實施時間拉長，學習效果卻降低。第三，根據問卷統計資料顯示，實驗組與對照組之學習態度無差異，但問題導向學習法卻能增加學習信心並提高課堂參與度。綜合上述發現，問題導向學習法並不適用於所有國中地理課程內容，抽象概念適合傳統講述教學，有議題性或實作性的內容則適用問題導向學習法，在課時限制之下，講述法搭配問題導向學習法能有效率教學，更能培養抽象思考及判斷能力，本研究所獲致的結果，可以提供國民中學地理教學之參考。 In recent years, educators have increasingly begun to use so-called “flipped classroom” teaching and learning techniques even though these are not necessarily suitable for every student. Problem-based Learning (PBL) is student-centered; students discuss true events, while teachers guide them and provide mini-lectures. As research in Taiwan has indicated that PBL is less frequently adopted in the teaching of human geography than in some other subjects, the primary purpose of this study was to investigate the teaching practice of PBL for seventh-grade human geography in Taiwanese schools. This research with a quasi-experimental design contrasted an experimental group subjected to PBL with a control group subjected to didactic teaching methods to explore whether PBL improves students' study scores and attitudes towards learning. The findings showed that the majority of students responded positively to PBL in several respects. First, students read the textbook more actively than previously and also demonstrated significant improvements in comprehension. Second, although the experimental group’s scores did not show obvious improvement, middle-level students demonstrated progress and seemed to benefit most from PBL. As time passed, however, the beneficial effects on overall learning apparently diminished. Third, questionnaire-derived data revealed no differences in attitudes towards learning between the experimental group and the control group, but the findings suggested that PBL may increase learners' confidence and participation in class. Based on this research, it is evident that PBL is not suitable for teaching all geography content at the junior high school level. Abstract concepts are better addressed using didactic teaching methods, while topical and practical content can be transmitted and absorbed effectively through PBL. Due to time limitations in class, a combination of didactic teaching and PBL is optimal and can improve students' critical thinking skills.